Permasalahan Penggunaan Trotoar Terhadap Pejalan Kaki Di Area Sekitar Universitas Jember - Alifia Aminingrum; Anisah Annuriyah Achmad; Jacinda Nathania Putri; Listyasari Hananie; Rafa Hanifah Isran; Rahma Nur Alia; Shofia Az’zahra; Agus Arifandi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The use of sidewalks as a place to trade for street vendors is a problem for road users, including pedestrians. Where this really disturbs pedestrians when they want to use the sidewalks or what is commonly referred to as the shoulder of the road to walk. The sidewalk itself is intended for pedestrians, not for people selling, let alone to close access for pedestrians. This happened around the Jember University Campus Area.